A bottleneck analysis in the IFRC supply chain. Issue 2 (7th October 2014) - Buddas, Henrietta
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to further the understanding of bottlenecks occurring when preparing for humanitarian operations in the humanitarian supply chain. The focus in this paper is set on the activities of aid supply procurement and aid consolidation into standardised deliveries of humanitarian aid. Design/methodology/approach – The paper follows a qualitative case study and builds a theoretical bottleneck analysis framework, using, e.g. the theory of constraints as an important building block. The case study as such involves the IFRC supply chain. Findings – The findings in the empirical study show that there is a need for long-term planning (practical and strategic planning) of the supply procurement, as well as organisational commitment in order to remove bottlenecks in a humanitarian operation. Research limitations/implications – The research framework built for the case study is applicable in similar future analyses of humanitarian supply chain operations and projects, as well as modifiable to other types of project or operation analyses. Practical implications – This paper gives a wide perspective insight into constraining bottleneck areas as well as areas of improvement in disaster preparedness. Additionally the paper provides an applicable tool for humanitarian practitioners to use for analysing process bottlenecks, to decide on corrective actions. Originality/value – The paper constructs a bottleneck analysis framework, which can be utilised beyond the humanitarian setting. Bottleneck analyses have not previously been conducted within the humanitarian context.